Screening cassava (Manihot esculenta crantz) for polyethelene glycol mediated osmotic stress in vitro - Ng, S.Y.C.; Ekanayake, I.J. (1997)
A description of cassava clones by their various mechanisms of tolerance to drought is useful in selecting parental clones tor hybridization and subsequent selection of clones from their progeny, which are targeted to various agroecological zones in the Sub-sahraran Africa. Evaluation of cassava germplasm in the field or in pots to water deficit stress is laborious, expensive, and time consuming. Dlurnal, periodic, and seasonal variations in water deficits and other climatic stress factors occurring at such times of water stress also complicate the detection of drought tolerant clones using field techniques. Development of in vitro testing methods may overcome some of these field constraints on effective screening for drought tolerance. A series of in vitro studies were conducted to test the response of cassava nodal cuttings to polyethylene glycol (PEG 8000 molecular weight) mediated osmotic stress. Clones tested had varying field drought tolerance responses. These were TMS 4 (2) 1425, TMS 4 (2)1425PI-2, TMS 91934, TMs 50395, TMS_ 84754, TMS0853, and TME 2. in vitro growth of nodal cuttings was totally inhibited at 0.5 MPa and -0.85 MPa growth media osmotic potentials. Two clones, TMS 50395.and TMS 908533, however, retained greenness at -0.5 MPa. Within the in vitro media osmotic potential range of -0.054 MPa and--0.21g MPa, clonal differences were noted for a range of growth paramelets, including stress index, suggesting that this technique could be used for used for preliminary screening of cassava germplasm.